Emergency department visits due to new psychoactive substances and other illicit drugs in Taiwan: preliminary results of the Taiwan Emergency Department Drug Abuse Surveillance (TEDAS) project. (3rd June 2022) - Lin, Chih-Chuan; Weng, Te-I; Ng, Chip-Jin; Shih, Chia-Pang; Hsu, Jui; Liao, Yuan-Chun; Yang, Chen-Chang; Fang, Cheng-Chung; ,
Abstract: Introduction: The use of new psychoactive substances (NPSs) has markedly increased worldwide; thus, it is important to monitor NPS-related effects. The Taiwan Emergency Department Drug Abuse Surveillance (TEDAS) project aims to assess the patterns of recreational drug use in patients presenting to emergency departments (EDs) across the country. Here, we report the preliminary results of this project. Methods: This observational study included the collection and analysis of urine samples and assessment of the clinical presentation of patients from 79 EDs across Taiwan. Clinical features were recorded through a questionnaire filled by attending doctors or nurses who collected urine samples for clinical diagnosis. Urine samples were analyzed for 110 drugs and metabolites using electrospray ionization liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: Between February and November 2019, a total of 2649 patients were enrolled for urine drug analysis. A total of 675 cases older than 12 years (males, n  = 480) had NPS or other illicit drugs detected in their urine samples. Overall, 1271 counts of drugs, among which 717 (56.4%) were NPS. At least one NPS was detected in 340 patients (50.4%), and 292 cases were positive for multiple drugs. The most frequently detected drug was methamphetamine/amphetamine, followed by synthetic cathinones, ketamine and its two analogs, and opioids. The most common drug combination was cathinones plus ketamine and/or its analogs ( n  = 56). Younger patients (OR = 3.3, p ≤.0001) and women (OR = 1.5, p  = .01) were more likely to have NPS detected in their urine samples. NPS-positive cases frequently experienced chest pain (OR = 2.6, p  = .03), tachycardia (OR = 2.6, p  = .0002), and suicide attempt/non-suicidal self-harm (OR = 1.8, p  = .004), whereas depressed consciousness (OR = 0.5, p  = .001) was less frequent among NPS-positive cases than among other illicit drug-positive cases. Conclusions: The TEDAS project provides a nationwide epidemiological profile of recreational drug use in Taiwan. More than half of the recreational drugs were NPSs, which were comprehensively detected using LC-MS/MS.